Preparation method and application of transparent polyurethane with high refractive index

High refractive index transparency was prepared by using photo-initiated reaction of 1,3-divinyltetramethyldisiloxane and 1,2-ethylenedithiol in polyurethane resin and chain extension reaction of isocyanate combined with composite catalysts. Polyurethane solves the problem of improving the performance of high sulfur content polyurethane resins in the prior art, and achieves high refractive index and excellent optical performance.

CN119241799APending Publication Date: 2025-01-03TAIYUAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527718.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing technology has problems of foreign technology blockade and slow domestic research and development in improving the performance of high-refractive index polyurethane resins, resulting in a lack of preparation of high-sulfur content polyurethane lenses.

Method used

Sulfur-containing soft segments are prepared by 1,3-divinyltetramethyldisiloxane and 1,2-ethylenedithiol under the photoinitiator benzoin dimethyl ether, followed by reaction with isocyanate and sulfur-containing chain extender , composite catalyst is used to optimize the synthesis of transparent polyurethane with high refractive index to improve its refractive index.

Benefits of technology

The refractive index of polyurethane was successfully improved, and the refractive index reached 1.6443 after the sulfur content increased, which significantly improved the optical performance of the material. The structural and performance advantages of the material were verified through characterization and analysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241799A_ABST
    Figure CN119241799A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of materials, in particular to a preparation method and application of transparent polyurethane with a high refractive index. The preparation method of the transparent polyurethane with the high refractive index comprises the following steps: (1) preparing a sulfur-containing soft segment crude product, namely preparing a sulfur-containing soft segment oligomer from 1, 3-divinyl tetramethyl disiloxane and 1, 2-dithiol under the catalysis of a photoinitiator and irradiation of an ultraviolet lamp; (2) purification of the sulfur-containing soft-segment crude product: pouring the sulfur-containing soft-segment crude product in the step (1) into low-temperature methanol for precipitation treatment, and performing centrifugal separation; purifying and drying overnight in a vacuum environment to obtain a sulfur-containing soft segment pure product; and (3) preparing polyurethane, namely preparing the high-refractive-index transparent polyurethane from the sulfur-containing soft-segment pure product prepared in the step (2), isocyanate, a sulfur-containing chain extender and a composite catalyst. The high-refractive-index transparent polyurethane prepared by the method has the advantages that the sulfur content is increased, the transparency and the refractive index are more excellent, and a basis is provided for further research on optical elements, coatings or optical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a preparation method and application of transparent polyurethane with a high refractive index. Background Art

[0002] Optical waveguide matrix materials refer to materials used as the basic structure or substrate for light transmission in optical waveguide devices. Polyurethane resin happens to be a material that meets such requirements and is widely used in optics, electronics, coatings and other fields. High refractive index polyurethane resin is one of the materials that meets this requirement. It has excellent optical properties, such as high refractive index, excellent transparency, and low dispersion performance. At the same time, compared with other optical waveguide matrix materials, polyurethane has the characteristics of adjustable control, which makes it have important application prospects in various optical components, coatings and optical devices.

[0003] Polyurethane was prepared by Professor Otto Bayer and his colleagues in 1937. Its main components are dihydroxyl functional groups, dithiol functional groups or more active hydrogen compounds (-OH and -SH) and diisocyanates or diisothiocyanates. It is obtained through polymerization reaction and has good wear resistance and optical properties. In order to better develop polyurethane optical resins with high refractive index characteristics, the researchers' research direction is mainly focused on how to design and synthesize new polyurethane raw materials with high sulfur content.

[0004] As a high-performance material, the properties of polyurethane resin mainly come from the hydroxyl (-OH) and isocyanate (-NCO) groups in its molecular structure. These unique groups give polyurethane resin excellent wear resistance, impact resistance and chemical resistance, making it an ideal choice for coatings, waterproof materials and sole materials. However, with the advancement of science and technology and the continuous expansion of the market, people have put forward higher requirements for the performance of polyurethane resin. Researchers have found that the addition of sulfur not only retains the original physical performance advantages of polyurethane resin, such as wear resistance, impact resistance and chemical resistance, but also greatly improves its optical performance refractive index. Thiopolyurethane is usually a reaction between a thiol (-SH) and an isocyanate (-NCO). Compared with conventional polyurethane, thiopolyurethane has a higher refractive index because the sulfur atom itself has a higher refractive index. However, due to foreign technology blockades and slow domestic research and development progress, there is a lack of this project. In order to fill this gap, this application conducts basic theoretical research and curing molding technology research to provide a theoretical basis for the preparation of high-refractive index sulfur-containing polyurethane lenses, further shorten the production cycle, and further improve the refractive index. Summary of the invention

[0005] In order to make up for the deficiencies of the prior art, the present invention provides a preparation method and application of transparent polyurethane with a high refractive index, and solves the problems existing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides one of the technical solutions:

[0007] A method for preparing transparent polyurethane with a high refractive index comprises the following steps:

[0008] (1) Preparation of sulfur-containing soft segment crude product

[0009] 1,3-divinyltetramethyldisiloxane and 1,2-ethanedithiol are catalyzed by a photoinitiator, benzoin dimethyl ether, and irradiated with an ultraviolet lamp to prepare a sulfur-containing soft segment oligomer; a crude sulfur-containing soft segment product is obtained;

[0010] (2) Purification of crude sulfur-containing soft segment products

[0011] The crude sulfur-containing soft segment product of step (1) is poured into low-temperature methanol for precipitation treatment, and then centrifuged; purified and dried overnight in a vacuum environment to obtain a pure sulfur-containing soft segment;

[0012] (3) Polyurethane preparation

[0013] The pure sulfur-containing soft segment in step (2) is mixed with isocyanate, a sulfur-containing chain extender and a composite catalyst to prepare a transparent polyurethane with a high refractive index.

[0014] Furthermore, in step (1) the preparation of the sulfur-containing soft segment, the molar ratio of 1,3-divinyltetramethyldisiloxane to 1,2-ethanedithiol is 1:1.2. Under this condition, 1,2-ethanedithiol is in excess, and an oligomer with thiol as the terminal group is obtained.

[0015] Furthermore, the preparation of the sulfur-containing soft segment in step (1) is as follows:

[0016] According to the above molar ratio, 1,3-divinyltetramethyldisiloxane, 1,2-ethanedithiol and photoinitiator benzoin dimethyl ether DMPA were added one by one into a pre-cooled and dried weighing bottle, and the bottle was quickly sealed; the sealed weighing bottle was placed under a UV lamp for irradiation, and the reaction was stirred thoroughly until the system gradually became viscous; and a crude sulfur-containing soft segment product was obtained.

[0017] Furthermore, the specific preparation of the sulfur-containing soft segment in step (1) is as follows:

[0018] 3.72 g of 1,3-divinyltetramethyldisiloxane, 2.26 g of 1,2-ethanedithiol and 0.04 g of photoinitiator dimethyl benzoate DMPA were added one by one into a pre-cooled and dried weighing bottle, and the bottle was quickly sealed; the sealed weighing bottle was placed under a UV lamp for irradiation, and the reaction was stirred thoroughly until the system gradually became viscous; and a crude sulfur-containing soft segment product was obtained.

[0019] The centrifugal separation speed in step (2) is 8000 r / min-10000 r / min; preferably, the centrifugal separation speed is 9000 r / min.

[0020] In step (3), the molar ratio of the pure sulfur-containing soft segment to isocyanate and sulfur-containing chain extender is 1:6:5, and the amount of the composite catalyst is 0.18% of the total system mass.

[0021] Furthermore, the isocyanate in step (3) is hydrogenated diphenylmethane diisocyanate; the sulfur-containing chain extender is 1,2-ethanedithiol or 1,4-butanediol; and the composite catalyst is a composite catalyst of triethylamine and dibutyltin dilaurate.

[0022] Furthermore, the mass ratio of triethylamine to dibutyltin dilaurate in the composite catalyst is 1:5.

[0023] Furthermore, the specific operation of step (3) is as follows:

[0024] S1 weighs the sulfur-containing soft segment pure product, isocyanate, sulfur-containing chain extender and composite catalyst according to the molar ratio of sulfur-containing soft segment pure product to isocyanate and sulfur-containing chain extender of 1:6:5 and the amount of catalyst is 0.18% of the total system mass; set aside;

[0025] S2: The weighed raw materials, including the pure sulfur-containing soft segment, isocyanate and composite catalyst, are placed in a beaker for heating and magnetic stirring, and prepolymerized for 6h-8h; in the later stage of prepolymerization, solvent N,N-dimethylformamide is added according to the viscosity to ensure the stable operation of the rotor during magnetic stirring;

[0026] After S3 prepolymerization, sulfur-containing chain extender is added in small amounts and multiple times, and solvent N,N-dimethylformamide is added depending on the viscosity to extend the chain until the reaction is complete, and then dried to obtain;

[0027] Wherein, in step S1, the sulfur-containing chain extender is 1,2-ethanedithiol; and the composite catalyst is triethylamine and dibutyltin dilaurate in a mass ratio of 1:5.

[0028] Furthermore, after S2 was prepolymerized for 6 h, the solvent N,N-dimethylformamide was added to ensure the stable operation of the rotor during magnetic stirring and to ensure that the thiol groups reacted completely to a greater extent.

[0029] Furthermore, S3 is dried and placed in a high temperature resistant silicone mold for complete drying.

[0030] Furthermore, in step S2, the magnetic stirring conditions are a temperature of 80° C. and a rotation speed n=500 r / min.

[0031] Furthermore, in step S3, the chain is extended for 3h.

[0032] Furthermore, the S2 prepolymerization reaction time is 8 hours, and the S3 chain extension reaction time is 3 hours.

[0033] Furthermore, the refractive index of the obtained high refractive index transparent polyurethane reaches 1.6443.

[0034] The present invention also provides a second technical solution:

[0035] Application of the high refractive index transparent polyurethane prepared by the preparation method described above in optical elements, coatings or optical devices.

[0036] Furthermore, the above-mentioned high refractive index transparent polyurethane is used in a solar concentrator, and the solar concentrator is a carbon quantum dot solar concentrator.

[0037] Furthermore, the carbon quantum dot solar concentrator is based on the sulfur-containing polyurethane matrix prepared in the present invention, and fluorescent carbon dots are introduced to prepare a polyurethane luminescent film material.

[0038] It is prepared by compounding carbon dots and the aforementioned high refractive index transparent polyurethane.

[0039] Beneficial effects of the present invention:

[0040] The present invention uses 1,2-ethanedithiol (EDT), 1,3-divinyltetramethylsiloxane (MM Vi ) was synthesized by mercapto-olefin click reaction under the catalysis of photoinitiator benzoin dimethyl ether (DMPA), and then a series of thiocarbamates with different sulfur contents SPU0 (S: 0%), SPU1 (S: 10.7%), SPU2 (S: 17.7%), SPU3 (S: 21.0%), SPU4 (S: 24.5%) were synthesized by reaction with hydrogenated diphenylmethane diisocyanate, sulfur-containing chain extender 1,4-butanediol and / or 1,2-ethanedithiol. The structures and properties of the above materials were characterized and analyzed by infrared spectrometer, ultraviolet spectrophotometer, X-ray diffractometer, Abbe refractometer, etc. The results show that the infrared spectrum shows that the mercapto, hydroxyl and isocyanate groups have all reacted completely, and the sulfur-containing polyurethane sample is successfully synthesized; the refractive index test shows that with the increase of sulfur content, the refractive index gradually increases, and the highest refractive index of SPU4 reaches 1.64429, which is 24.3% higher than that of SPU0; the X-ray diffraction peak shows that the molecular order of sulfur-containing polyurethane decreases; the ultraviolet transmittance test results show that the yellowness and transmittance of single soft segment and single hard segment polyurethane samples are better than those of mixed system polyurethane; in the contact angle test, the Si-O bond increases the contact angle of the sample, showing a certain hydrophobicity.

[0041] The present invention designs and regulates the sulfur content in the polyurethane structure based on the structure-activity relationship in order to achieve its high refractive index performance. On the one hand, sulfur-containing soft satin is synthesized through the thiol-ene click reaction, and on the other hand, a sulfur-containing chain extender is selected to further increase the sulfur content of the system. By optimizing the synthesis reaction process, a SPU4 sample with a high sulfur content (24.5%) is finally obtained, showing remarkable excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a schematic diagram of the polyurethane reaction principle of the sulfur-containing system of the present invention;

[0043] Figure 2 This is a schematic diagram of the preparation principle of the silicon-sulfur soft segment of the present invention;

[0044] Figure 3 The prepolymerization process changes of the sample SPU4 polyurethane of the present invention at different times;

[0045] Figure 4 The polyurethane samples SPU0-SPU4 of the present invention are;

[0046] Figure 5 The contact angle test results of the sulfur-containing polyurethane sample of the present invention;

[0047] Figure 6 is the ultraviolet transmittance of the sulfur-containing polyurethane sample of the present invention;

[0048] Figure 7 The silicon-sulfur soft segment, MM Vi , infrared spectrum of EDT;

[0049] Figure 8 This is the infrared spectrum of the sulfur-containing polyurethane sample of the present invention;

[0050] Fig. 9 The figure is the XRD diffraction spectrum of the sulfur-containing polyurethane sample of the present invention. DETAILED DESCRIPTION

[0051] In order to clearly illustrate the technical features of the present invention, the present invention is described in detail below through specific implementation methods in conjunction with the accompanying drawings.

[0052] The instruments, reagents, materials, etc. involved in the following embodiments, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0053] The sulfur-containing polyurethane formulas of different sulfur contents involved in the embodiments of the present invention are shown in Table 1. In Table 1, the samples are named according to their sulfur contents, SPU0 (S: 0%), SPU1 (S: 10.7%), SPU2 (S: 17.7%), SPU3 (S: 21.0%), and SPU4 (S: 24.5%).

[0054] Table 1 Sulfur-containing polyurethane formulation

[0055]

[0056] Example 1

[0057] A method for preparing transparent polyurethane with a high refractive index comprises the following steps:

[0058] (1) Preparation of sulfur-containing soft segment crude product

[0059] The sulfur-containing soft segment oligomer (i.e., silicon-sulfur soft segment) was prepared by mercaptoene click reaction with a molecular weight of 2600 g / mol. Figure 2 The process requires precise operation to ensure the ideal conversion rate and purity at each step.

[0060] First, according to the precise ratio, 3.72 g (20 mmol) of 1,3-divinyltetramethyldisiloxane (MM Vi ), 2.26 g (24 mmol) 1,2-ethanedithiol (EDT) and a trace amount of 0.04 g photoinitiator DMPA were added one by one into a pre-cooled and dried 25 ml weighing bottle, and then the weighing bottle was quickly sealed to prevent contamination by moisture or other impurities in the air; next, the sealed weighing bottle was placed about 3 to 4 cm under a UV lamp to ensure that the reactants could be evenly irradiated by ultraviolet light, and the reaction was fully stirred for 15 minutes; during the reaction, it can be observed that the system gradually becomes viscous, which is an intuitive manifestation of the polymerization reaction; at this time, a crude product containing sulfur soft segment has been successfully prepared;

[0061] (2) Purification of crude sulfur-containing soft segment products

[0062] The small molecular impurities and the remaining photoinitiator in the crude sulfur-containing soft segment product of step (1) are removed to improve the purity, specifically: the crude product obtained in step (1) is directly poured into about 20 ml of low-temperature methanol for precipitation treatment for 30 minutes; the low-temperature methanol can effectively separate the high molecular weight sulfur-containing soft segment from the low molecular weight impurities, and also helps to remove the photoinitiator; after the precipitation is completed, the methanol and the precipitate are separated by centrifugation at a speed of 9000 r / min to obtain a relatively pure sulfur-containing soft segment product; finally, the sulfur-containing soft segment is placed in a vacuum oven at room temperature, and further purified and dried overnight in a vacuum environment; finally, a pure and dry sulfur-containing soft segment product is obtained;

[0063] (3) Polyurethane preparation

[0064] The pure sulfur-containing soft segment in step (2) is mixed with isocyanate, a sulfur-containing chain extender, a catalyst and N,N-dimethylformamide to prepare a transparent polyurethane with a high refractive index.

[0065] In this step, according to the dosage standard of "the molar ratio of pure sulfur-containing soft segment to isocyanate and sulfur-containing chain extender is 1:6:5, and the catalyst accounts for 0.18% by mass of the reaction system", 5 polyurethanes SPU0, SPU1, SPU2, SPU3, and SPU4 with different refractive indices were prepared by adding or not adding polytetrahydrofuran (PTMG-1000), adjusting the type and dosage of the sulfur-containing chain extender, and optimizing the catalyst. For details, see the formula in Table 1.

[0066] The experimental raw materials were weighed according to R (-NCO / -SH) = 1.05, silicon-sulfur soft segment: isocyanate: sulfur-containing chain extender = 1:6:5 (molar ratio).

[0067] This example uses sample SPU4 as an example. The total amount of the drug is about 5.82g. Weigh 3.2g of silicon-sulfur soft segment, 2.04g of 4,4-dicyclohexylmethane diisocyanate (HMDI), 0.58g of 1,2-ethanedithiol (EDT), 1.8μl of 0.0017g of triethylamine (TEA) and 11.5μl of 0.00873g of dibutyltin dilaurate (DBTDL) with a pipette. (The other four groups of samples weigh the corresponding drugs according to the corresponding molar ratio)

[0068] Experimental steps: First, the weighed raw materials - silicon-sulfur soft segment (i.e. the prepared pure sulfur-containing soft segment), isocyanate, TEA and DBTDL (composite catalyst) are placed in a 50ml beaker, a rotor is placed in the beaker, sealed with plastic wrap (to prevent moisture in the air from entering and affecting polymerization), and placed on a magnetic heating stirrer. The temperature T = 80 ° C and the speed n = 500r / min are set for prepolymerization for 8 hours; after the prepolymerization is completed, the sulfur-containing chain extender - 1,2-ethanedithiol (EDT) is added in small amounts and multiple times, and the solvent N,N-dimethylformamide (DMF) is added depending on the viscosity of the system. The chain is extended for about 3 hours until the reaction is complete, and then placed in a high-temperature resistant silicone mold for complete drying, about 24 hours.

[0069] See also Figure 3, which is the prepolymerization process of the sample SPU4 polyurethane reaction. The pictures show the color states of the reaction system corresponding to 0h, 1.5h, 3h, 4h, 5h, 6h, 7h, and 8h. It is not difficult to find that as time goes on, the color of the silicon-sulfur soft segment reaction system will gradually deepen as the reaction time increases, from colorless and transparent to yellow and transparent, and finally to dark brown. At the same time, it is found that the small bubbles are also increasing with the passage of time. After prepolymerization for 6h, the viscosity of the system will increase significantly. When appropriate, the solvent DMF needs to be added to ensure the smooth operation of the rotor and to ensure that the thiol group reacts completely to a greater extent. After the reaction reaches 8h, add a small amount of sulfur-containing chain extender EDT dropwise each time, and add DMF depending on the viscosity of the system. After 3h, take it out and dry it in the oven for 24h.

[0070] Example 2-Example 5

[0071] The remaining four groups of experiments are samples SPU0 to SPU3, which are obtained by repeating the above preparation and experimental steps of Example 1 according to the formula and dosage in Table 1. The differences between the prepolymerization reaction and the chain extension reaction and SPU4 in Example 1 are shown in Table 2.

[0072] Table 2 Reaction time of polyurethane in SPU system

[0073]

[0074] Since the activity of thiol is lower than that of hydroxyl, the reaction is improved by extending the reaction time and using a composite catalyst. Specifically, the prepolymerization time of the reaction raw materials is extended from 2h to 8h for the preparation of sample SPU0, and the chain extension time is extended from 1.5h to 3h; the use of a composite catalyst (0.18%, TEA:DBTDL=1:5), amine catalysts can accelerate the reaction rate of thiol, and the system prepolymerization for 6h can reach the viscosity state of the system with only DBTDL added for 8h, so the examples are all prepared using a composite catalyst system.

[0075] See also Figure 4 The pictures from left to right are the finished products of SPU0, SPU1, SPU2, SPU3, and SPU4. From a macroscopic point of view, the prepared sulfur-containing polyurethanes all have good transparency (text can be clearly seen through), but it can also be seen that with the introduction of silicon and sulfur elements, the color of the prepared samples becomes yellow to varying degrees.

[0076] Experimental test:

[0077] 1. Refractive index of polyurethane film samples of the present invention

[0078] Table 3 Refractive index of sulfur-containing polyurethane film samples

[0079]

[0080] It can be seen from Table 3 that as the sulfur content of the sample gradually increases, the refractive index is greatly improved. Since the refractive index above 1.6 is called a high refractive index, the average refractive index of the SPU4 system prepared in the present invention is 1.64429, which verifies that the introduction of the silicon-sulfur soft segment and the sulfur-containing chain extender EDT in the method of the present invention can further improve the refractive index of the polyurethane film sample, providing reliable experimental support for the subsequent research on fluorescent optical waveguide film materials.

[0081] 2. Contact angle test

[0082] Generally, the introduction of Si element will affect the surface hydrophilicity and hydrophobicity of the material. In order to test the wetting properties of the solid surface, the contact angle test was carried out.

[0083] The results are as follows Figure 5 As shown, it can be observed that with the introduction of silicon-sulfur soft segments, the contact angle will gradually increase. SPU0 and SPU1 samples show a certain hydrophilicity, and the contact angles are less than 90°. SPU2, SPU3, and SPU4 samples show hydrophobicity, and the contact angles are greater than 90°. This reflects the successful synthesis of sulfur-containing polyurethane from the side, and the Si-O bond will increase its surface tension on the polyurethane sample, showing a certain hydrophobicity.

[0084] 3. UV transmittance of polyurethane film samples of the present invention

[0085] Table 4 UV transmittance and yellowness of sulfur-containing polyurethane samples

[0086]

[0087]

[0088] As shown in Table 4, with the increase of yellowness, the UV transmittance at 500nm decreases. The higher the yellowness, the lower the UV transmittance. The sample with the lowest transmittance is SPU1, which is 80.76%. This sample is brittle and has a high yellowness of 20.1. The sample with the highest transmittance is SPU0, which is 89.41% and has a yellowness of 4.9.

[0089] Combined with Table 4, Figure 6 It can be seen that in the visible light region of 400-700nm, as the wavelength becomes shorter, the transmittance decreases. Among them, as the sulfur content increases, the ultraviolet transmittance of SPU0, SPU2, and SPU4 samples first decreases and then increases, and the yellowness first increases and then decreases; SPU1 and SPU3 samples have a large yellowness and poor transmittance. This shows that the polyurethane synthesized by a single soft segment and a single hard segment has better transmittance and yellowness than the mixed system.

[0090] 4. Infrared testing, X-ray diffraction

[0091] In order to characterize the silicon-sulfur soft segment and the functional groups of the synthetic polyurethane raw materials, we conducted infrared testing, and the absorption spectrum was as follows Figure 7 As can be seen in the figure, the silicon-sulfur soft segment and 1,3-divinyltetramethylsiloxane MM Vi The absorption peaks of 1,2-ethanedithiol (EDT) are basically consistent, indicating that the silicon-sulfur soft segment was successfully synthesized.

[0092] In order to characterize whether the thiol (-SH), isocyanate (-NCO), and hydroxyl (-OH) functional groups have reacted completely, we performed infrared spectroscopy analysis, such as Figure 8 As shown. Among them, at 3200-3600cm -1 In the wave number range, except for 3310cm -1 Except for the infrared absorption peak of NH, there are no other characteristic peaks, indicating that the hydroxyl (-OH) reaction is complete; 2920, 2850cm -1 The peaks at 2500-2600cm are the CH stretching vibration peaks of -CH3 and -CH2. -1 There is no absorption peak at 2200-2250cm -1 No obvious absorption peaks appeared, indicating that the isocyanate group (-NCO) had reacted completely; 780, 838 cm -1 The infrared absorption peak of CS bond is at 1.37°. Therefore, the sulfur-containing polyurethane film sample was successfully synthesized.

[0093] In order to characterize the crystallinity of sulfur-containing polyurethane film samples, wide-angle X-ray diffraction of 10-40° was performed. Fig. 9 It can be seen that a strong peak appears in the area around 2θ of 20°, among which SPU0 has the highest peak, indicating that its internal polymer chain has good regularity. However, with the introduction of silicon-sulfur soft segments, the peak intensity will decrease, but the position of the peak is not much different. At the same time, with the increase of sulfur content, the peak intensity also gradually decreases, indicating that the introduction of silicon-sulfur soft segments and sulfur-containing chain extender EDT does not change the crystal form of polyurethane crystals, but the decrease in the crystallization peak intensity shows that with the increase of sulfur content, the orderly arrangement of polyurethane macromolecular chains is restricted to a certain extent, and the regularity of the molecular chain has decreased to varying degrees, confirming its excellent refractive index.

[0094] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing a transparent polyurethane with a high refractive index, characterized in that: The steps are as follows: (1) Preparation of sulfur-containing soft segment crude product 1,3-divinyltetramethyldisiloxane and 1,2-ethanedithiol are catalyzed by a photoinitiator, benzoin dimethyl ether, and irradiated with an ultraviolet lamp to prepare a sulfur-containing soft segment oligomer; a crude sulfur-containing soft segment product is obtained; (2) Purification of crude sulfur-containing soft segment products The crude sulfur-containing soft segment product of step (1) is poured into low-temperature methanol for precipitation treatment, and then centrifuged; purified and dried overnight in a vacuum environment to obtain a pure sulfur-containing soft segment; (3) Polyurethane preparation The pure sulfur-containing soft segment obtained in step (2) is mixed with isocyanate, a sulfur-containing chain extender and a composite catalyst to prepare a transparent polyurethane with a high refractive index.

2. The method for preparing a transparent polyurethane with a high refractive index according to claim 1, characterized in that: The preparation of the sulfur-containing soft segment in step (1) is as follows: 1,3-divinyltetramethyldisiloxane and 1,2-ethanedithiol in a molar ratio of 1:1.2, and photoinitiator dimethyl benzoate DMPA are added one by one into a pre-cooled and dried weighing bottle, and the bottle is quickly sealed; the sealed weighing bottle is placed under a UV lamp for irradiation, and the reaction is stirred thoroughly until the system gradually becomes viscous; a crude sulfur-containing soft segment product is obtained; Step (2) centrifugal separation speed 8000r / min-10000r / min; In step (3), the molar ratio of the pure sulfur-containing soft segment to isocyanate and sulfur-containing chain extender is 1:6:5, and the amount of the composite catalyst is 0.18% of the total system mass.

3. The method for preparing a transparent polyurethane with a high refractive index according to claim 1, characterized in that: In step (3), the isocyanate is hydrogenated diphenylmethane diisocyanate; the sulfur-containing chain extender is 1,2-ethanedithiol and / or 1,4-butanediol; and the composite catalyst is a composite catalyst of triethylamine and dibutyltin dilaurate.

4. The method for preparing a transparent polyurethane with a high refractive index according to claim 3, characterized in that: The mass ratio of triethylamine to dibutyltin dilaurate in the composite catalyst is 1:

5.

5. The method for preparing a transparent polyurethane with a high refractive index according to claim 1, characterized in that: The specific operation of step (3) is as follows: S1: weigh the pure sulfur-containing soft segment, isocyanate, sulfur-containing chain extender and composite catalyst according to the molar ratio of pure sulfur-containing soft segment to isocyanate and sulfur-containing chain extender of 1:6:5 and the amount of composite catalyst is 0.18% of the total system mass; set aside; S2: The weighed raw materials, including the pure sulfur-containing soft segment, isocyanate and composite catalyst, are placed in a beaker for heating and magnetic stirring, and prepolymerized for 6h-8h; in the later stage of prepolymerization, solvent N,N-dimethylformamide is added according to the viscosity to ensure the stable operation of the rotor during magnetic stirring; After S3 prepolymerization, sulfur-containing chain extender is added in small amounts and multiple times, and solvent N,N-dimethylformamide is added depending on the viscosity to extend the chain until the reaction is complete, and then dried to obtain; Wherein, in step S1, the sulfur-containing chain extender is 1,2-ethanedithiol; and the composite catalyst is triethylamine and dibutyltin dilaurate in a mass ratio of 1:

5.

6. The method for preparing a transparent polyurethane with a high refractive index according to claim 5, characterized in that: The magnetic stirring conditions in step S2 are temperature 80° C. and rotation speed n=500 r / min.

7. The method for preparing a transparent polyurethane with a high refractive index according to claim 5, characterized in that: The chain extension period in step S3 is 3h.

8. The method for preparing a transparent polyurethane with a high refractive index according to claim 5, characterized in that: The S2 prepolymerization reaction time is 8 h, and the S3 chain extension reaction time is 3 h.

9. The method for preparing a transparent polyurethane with a high refractive index according to any one of claims 1 to 8, characterized in that: The refractive index of the prepared high refractive index transparent polyurethane reaches 1.6443.

10. Use of the high refractive index transparent polyurethane prepared by the preparation method according to any one of claims 1 to 8 in optical elements, coatings or optical devices.